Pramoedya Ananta Toer dan manifestasi karya sastra - Mahendra, Daniel; Pramoedya Institute; Penerbit Malka (Bandung : Malka, 2004)
Literary criticism on Pramoedya Ananta Toer's works
Includes bibliographical references
Keywords: Indonesian literature -- Addresses, essays, lectures